2000
DOI: 10.1385/jmn:14:1-2:017
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Analysis of Neurosecretory Cells in the Antennae of the Mosquito, Culex Salinarius (Diptera: Culicidae)

Abstract: An antiserum raised against the peptide, culetachykinin II, immunocytochemically detected a group of neurosecretory cells in the first flagellar segment of the antennae of both males and females of the mosquito, Culex salinarius. This is the first insect species in which neurosecretory cells have been found in the antennae. The ultrastructure of these antennal neurosecretory cells (ANC) is described, as well as their relationship to other neurons in the antennae and antennal lobe of the mosquito. These tachyki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Tracing of axonal projections revealed that these neurons projected into the flagellar axon bundle. No cell bodies were found, and we speculate that these neurons most likely are neuropeptidergic neurons previously described by Meola et al (1998Meola et al ( , 2000 and Meola and SittertzBhatkar (2002), and by extension should have their cell bodies located within the flagellum.…”
Section: Interneurons Innervating Al Glomerulisupporting
confidence: 53%
See 1 more Smart Citation
“…Tracing of axonal projections revealed that these neurons projected into the flagellar axon bundle. No cell bodies were found, and we speculate that these neurons most likely are neuropeptidergic neurons previously described by Meola et al (1998Meola et al ( , 2000 and Meola and SittertzBhatkar (2002), and by extension should have their cell bodies located within the flagellum.…”
Section: Interneurons Innervating Al Glomerulisupporting
confidence: 53%
“…The presence of 1) neuroendocrine cells, with dendritic arborizations in AL glomeruli, that form axo-dendritic synapses with ORNs in the antenna (Meola et al, 1998(Meola et al, , 2000Meola and Sittertz-Bhatkar, 2002; present study), and 2) a synaptic neuropil within the antennal nerve, where ORNs may make synaptic contacts with each other and/or with other cells have, however, not previously been reported in other groups of insects, and may be unique to mosquitoes. These structural peculiarities indicate a vital requirement of rapid fine tuning of signals acquired by this system and also implicate the need for a more longterm effector.…”
Section: Glomerular Organization Of the Al Of Aedes Aegyptimentioning
confidence: 53%
“…For instance, it has been shown that glomeruli change in size, depending on age and behavioral tasks in Drosophila (Mistry et al 2000) and honey bee (Sigg et al 1997;Winnington et al 1996). Other interneurons that are candidates for comparison in our Cotesia model system are peptidergic neurons containing tachykinins as described in the blowfly (Lundquist et al 1994) and the mosquito (Meola et al 2000). Our parasitoid wasps offer a good model system to study this phenomenon further.…”
Section: Applications Of the 3d Mapmentioning
confidence: 96%
“…Other potential underlying neuronal mechanisms of the observed behavioural sensitization may involve a general neuromodulatory network in the antennal lobe (e.g. Sachse and Galizia, 2002), or feedback neurons from the antennal lobe to the OSNs, a unique neuromodulatory pathway in mosquitoes (Meola et al, 2000;Meola and SittertzBhatkar, 2002;Bäcker, 2002).…”
Section: Sensitizationmentioning
confidence: 99%